KEMAMPUAN BERPIDATO SISWA KELAS IX SMP IT AL- IHSAN BOARDING SCHOOL KABUPATEN KAMPAR - Rika Ropita; Auzar Auzar; Hermandra Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study discusses the ability to speak especially to know the score or level of speech ability of students of IX SMP IT Al-Ihsan Boarding School Kampar District. The aspects studied in this study are the accuracy of pronunciation, accuracy of intonation, and appropriate expression in the speech. This study aims to describe data results or scores obtained by junior high school students IT Al-Ihsan Boarding School in a speech. Data or object in this research is the students of class IX SMP IT Al-Ihsan Boarding School Kampar District. The method used in this research is quantitative method that is processed by statistical count. The data in this study were analyzed by using statistical count begins with normality test using lilifors test, then using two different samples of one sample. Data collection techniques in this study is a direct test technique. Judging from the ability to deliver a grade IX students of SMP IT Al-Ihsan Boarding School Kampar District included into the category of good or moderate with an average value 81,83.Keywords: Speech, Pronunciation, Intonation, Ekspression